Phonics-Based Contextual Learning for Early Reading Development in Students with Intellectual Disabilities - Suwarsih, Ati; Pujaningsih, Pujaningsih (Papanda Publisher, 2025)
Students with intellectual disabilities face significant challenges in developing early reading skills, often due to inadequate instructional approaches that fail to address their specific learning needs. This study investigated the effectiveness of phonics-based contextual learning in improving early reading skills among fourth-grade students with intellectual disabilities. A classroom action research design following the Kemmis and McTaggart spiral model was employed with three participants (aged 9 years) with mild intellectual disabilities at State Elementary School 013 Muara Wahau, Indonesia. The intervention consisted of two cycles, each containing three 90-minute sessions incorporating systematic phonics instruction integrated with contextual learning strategies. Pre- and post-intervention assessments measured reading performance using CV and CVCV word pattern recognition tasks. Data were analyzed using descriptive statistics with success criteria set at 85% achievement. All participants demonstrated substantial improvements in reading performance. Baseline scores ranged from 0-20%, progressing to 60% (Cycle I) and ultimately achieving 80-100% (Cycle II). AL achieved 100% proficiency, while R and ZN both reached 80% proficiency. Qualitative observations revealed enhanced student engagement, confidence, and independent learning behaviors throughout the intervention period. Phonics-based contextual learning proved highly effective for improving early reading skills in students with intellectual disabilities. The intervention's success demonstrates the potential of combining systematic phonics instruction with contextually meaningful learning experiences in classroom settings. These findings contribute valuable evidence supporting inclusive educational practices and provide a practical framework for literacy instruction in this population.